2021
DOI: 10.1111/joim.13420
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging phenotypes of CSF1R‐related leukoencephalopathy: Systematic review, meta‐analysis, and imaging recommendations

Abstract: Benjamin V. Ineichen and Tobias Granberg shared the last authorship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 104 publications
1
8
0
Order By: Relevance
“…In the deeper cortex and cerebral white matter, the activated microglia were accumulated in the relatively preserved areas but not in the affected areas and exhibited abnormal morphologies and spatial restriction due to CSF1R mutation ( Tada et al, 2016 ). These pathological findings characterized by the region-specific distribution of the activated microglia were consistent with the structural brain MRI findings of the current and previous studies ( Mao et al, 2020 ; Mickeviciute et al, 2022 ), i.e., significant abnormal signals in the deep white matter of the frontoparietal lobe and corpus callosum, revealing the potential relationship between the number and functional changes in the microglia induced by CSF1R mutation and deep white matter degeneration.…”
Section: Discussionsupporting
confidence: 91%
“…In the deeper cortex and cerebral white matter, the activated microglia were accumulated in the relatively preserved areas but not in the affected areas and exhibited abnormal morphologies and spatial restriction due to CSF1R mutation ( Tada et al, 2016 ). These pathological findings characterized by the region-specific distribution of the activated microglia were consistent with the structural brain MRI findings of the current and previous studies ( Mao et al, 2020 ; Mickeviciute et al, 2022 ), i.e., significant abnormal signals in the deep white matter of the frontoparietal lobe and corpus callosum, revealing the potential relationship between the number and functional changes in the microglia induced by CSF1R mutation and deep white matter degeneration.…”
Section: Discussionsupporting
confidence: 91%
“…Besides, sagittal reconstructions of CT and 7 T MRI are helpful to demonstrate calcifications. 33,34 In addition, the DWI sequences of all patients in this study showed constant high signals in bilateral abnormal white matter, suggesting that abnormalities on the DWI sequences are an important clue for the diagnosis and differential diagnosis of CRD. DWI is more sensitive to reflect the changes in the microstructure of the white matter and can detect the changes in the white matter at an earlier stage than the T2-FLAIR sequences.…”
Section: Discussionmentioning
confidence: 56%
“…In the retrospective study in Japan, the patients mostly received 1‐mm thin‐layer CT scans, whereas in this study, the CT scans conducted in the patients were all plain scans. Besides, sagittal reconstructions of CT and 7 T MRI are helpful to demonstrate calcifications 33,34 …”
Section: Discussionmentioning
confidence: 99%
“…3 Although spinal cord involvement has only been reported in a few cases of CSF1R-related leukoencephalopathy, a systematic study of spinal cord findings in this disorder has not been undertaken to date. 9 Lesions may involve the lateral corticospinal tracts and diffusion restriction may be present in the spinal cord lesions as well. 9,10 In our case, spinal cord MRI was remarkable for short-segment focal hyperintensities in the right lateral cord at C2-3 and mid-C3 levels (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…9 Lesions may involve the lateral corticospinal tracts and diffusion restriction may be present in the spinal cord lesions as well. 9,10 In our case, spinal cord MRI was remarkable for short-segment focal hyperintensities in the right lateral cord at C2-3 and mid-C3 levels (Figure 2). Such spinal lesions are highly characteristic of MS and likely contributed to misdiagnosis in our case.…”
Section: Discussionmentioning
confidence: 99%